Effectiveness of Health Education using the PASTORA Application on Early Cancer Detection - Aji, Setyo (PT. Riset Press International, 2023)
Women's reproductive health problems, especially cancer, are health problems faced by women in the world , including in Indonesia. Nurses as an integral part of health services have the responsibility to carry out health promotion and innovate in developing health promotion media, especially during the Covid-19 pandemic. The purpose of this activity is to find out the differences in women's knowledge about early detection of cancer after health education using online media: the PASTORA application. The PASTORA application is an alternative media to increase health knowledge independently and complete it with online consultations with professional health workers. This research method is descriptive quantitative with participants in education totaling 105 women of reproductive age from four provinces in Indonesia, the education process was facilitated by 3 lecturers from the Faculty of Nursing and 16 students participating in the Virtual Integrative KPM at Gajah Mada University. The activity process includes the preparation, implementation and evaluation stages. Before and after education, a pre- posttest was carried out consisting of 15 questions. The results of the analysis of the test showed an increase in knowledge which was marked by an increase in pre-posttest scores for 94 (89.5%) participants, a fixed score of 7 (6.7%) and a decrease in value of 4 (3.8%). The PASTORA application based on Android technology is proven to increase women's knowledge about early cancer detection. It is necessary to develop the PASTORA application with IOS technology to increase the reach of female users in Indonesia. The PASTORA application can be used by nurses as an alternative medium for conducting reproductive health education for women.